Models of modern information economy : conceptual contradictions and practical examples - Sukhodolov, Alexander P.; Popkova, Elena G.; Litvinova, Tatiana N. (Emerald Publishing Limited, 2018)
The concept of an information economy is considered by some to be a new branch of economic theory, and by others as the next stage of development for an economy post-industrialization. Leading and developing economies are seeking to quickly develop a functional information economy in order to help overcome the consequences of the global financial crisis and ensure high global economic competitiveness. This book analyzes modern conceptual models of information economies, highlighting and examining their systemic contradictions and failings. It explores the disconnection between the readiness of the technical infrastructure for forming and developing the information economy, and an unprepared institutional and societal structure that is therefore unable to implement these processes and models. The editors present different approaches to solving these methodological and practical contradictions and lay out future models across different international contexts. They also provide recommendations for optimizing their theoretical model and improving its implementation in modern economic systems.